Prospects for the UK Economy. (August 2014) - Kirby, Simon; Meaning, Jack; Warren, James
Abstract : The production of this forecast is supported by the Institute's Corporate Members: Bank of England, HM Treasury, Mizuho Research Institute Ltd, Santander (UK) plc and by the members of the NiGEM users group.